Cover Image: Volume 22, Issue 3. Issue 3 (5th May 2020) - James Cooper, W.; VanHall, Rachel; Sweet, Elly; Milewski, Holly; DeLeon, Zoey; Verderber, Amy; DeLeon, Adrian; Galindo, Demi; Lazono, Orissa
Abstract : The cover image is based on the Original Article Functional morphogenesis from embryos to adults: late development shapes trophic niche in coral reef damselfishes by W. James Cooper, Orissa Lozano, Elly Sweet et al., https://doi.org/10.1111/ede.12321 .